Analisis Tingkat Kesehatan Bank Menggunakan Metode RGEC (Risk Profile, Good Corporate Governance, Earnings And Capital) pada Panin Bank Syariah Periode 2016-2021 - fahmialik fahmialik (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2023)
The purpose of this study was to determine the health of Panin Bank Syariah in the period 2016-2021 using the RGEC method with data derived from the annual financial statements of Panin Bank Syariah. The results showed that Panin Syariah Bank obtained the very healthy predicate on the CAR ratio. Meanwhile, the ratio of NPF and NI obtained a healthy predicate. In the ratio of FDR and PDN, the predicate is quite healthy. As well as the ratio of ROA, ROE and BOPO obtained the predicate less healthy. In this way, overall, the average soundness level of Panin Syariah Banks as measured by the RGEC method and various existing ratios. It can be said that Panin Bank Syariah is in a fairly healthy predicate. Panin Syariah Banks need to make improvement efforts in order to achieve safe bank health. Keywords: bank health, financial statements, RGEC, Panin Islamic Bank.